'Zones of contention' in industrial relations: Framing pluralism as praxis. (April 2021) - Dobbins, Tony; Hughes, Emma; Dundon, Tony
This article addresses debates in contemporary industrial relations about practical application of pluralism . We compare the potential efficacy of 'radical-pluralism' and 'neo-pluralism'. Data comes from analysis of employment relationships in two unionised public transport sector organisations, in the comparative country contexts of the UK and Republic of Ireland. It is argued that radical-pluralist framing of the employment relationship is better equipped than neo-pluralism to provide deeper and contextually sensitive understandings of the realities of unequal employment relationships. Desired (pluralist) democratic values differ from real world application of joint regulation (praxis). This raises implications regarding constraints on state regulation and public policy goals institutionalising pluralism as fluid and uneven praxis.